Short-term Oral Nitrite Administration Decreases Arterial Stiffness in Both Trained and Sedentary Wistar Rats - Souza, Thiago Pereira [UNESP]; Tardelli, Lidieli Pazin [UNESP]; Nicoletti, Rafael Antunes [UNESP]; Jacomini, Andre Mourao [UNESP]; Martins, Gabriel Francisco de Mello [UNESP]; Pinheiro, Lucas Cezar; Tanus-Santos, Jose Eduardo; Amaral, Sandra Lia do [UNESP]; Zago, Anderson Saranz [UNESP] (Arquivos Brasileiros Cardiologia, 2024)
Background: Nitric Oxide (NO) plays an important role in blood pressure (BP) regulation, acting directly on peripheral vascular resistance through vasodilation. Physical training (via eNOS/NO) and intake of nitrite have been considered major stimuli to increase NO. Objective: We examined the effects of oral nitrite administration and aerobic exercise training on BP and arterial stiffness in Wistar rats. Methods: Thirty-nine (39) young male Wistar rats were divided into the following groups (n = 9 or 10 per group): Sedentary-Control (SC), Sedentary-Nitrite (SN), Trained-Control (TC), and Trained-Nitrite (TN). They were submitted to aerobic physical training on treadmills for 8 weeks (50-60% of physical capacity, 1h/day, 5 days/week) or kept sedentary. In the last 6 days of training, oral nitrite was administered (15 mg/Kg by gavage). BP, arterial stiffness, and plasma and tissue nitrite concentrations were assessed after the training and oral nitrite administration period. The significant level was defined as p < 0.05. Results: Oral administration of nitrite was effective in reducing arterial stiffness values (TN,-23%; and SN,-15%). Both groups that had only one type of intervention showed lower systolic BP compared with control (TC vs. SC,-14.23; and SN vs. SC,- 12.46). Conclusion: We conclude that short-term oral administration for 6 days and an aerobic physical training program promote several hemodynamic benefits in male Wistar rats, such as improvements in arterial stiffness and BP. These responses suggest that physical training and sodium nitrite supplementation can be alternatives for the prevention and treatment of hypertension.
Keywords: Nitric Oxide; Nitrites; Exercise; Pulse Wave Analysis; Hypertension